Tandem solar cell and method of manufacturing same
By using ITO composed of SnO2 and In2O3 in a composite layer of a series solar cell, the efficiency reduction problem caused by the shunt path is solved, and the absorption rate is reduced in the short wavelength range is reduced, and the current value and efficiency are improved.
Patent Information
- Application Number
- CN202380067285.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-21
- Filing Date
- 2023-09-15
- Publication Date
- 2025-04-18
AI Technical Summary
When the horizontal conductivity of the composite layer is low, existing series solar cells are prone to generate shunt paths, resulting in reduced efficiency and a high absorption rate in the short wavelength range, limiting the increase of the current value.
By using ITO composed of SnO2 and In2O3 with a weight ratio of 18 to 21:79 to 82 as a transparent conductive film, the thin layer resistance of the composite layer is increased, the conductivity and electron mobility are reduced, thereby minimizing the occurrence of the shunt path and reducing the absorption rate in the short wavelength range.
The efficiency of the series solar cells is effectively improved, the efficiency reduction caused by the shunt path is reduced, and the current value is increased when applied to the series solar cells.
Smart Images

Figure CN119856594A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0119088, filed on September 21, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] The present invention relates to a tandem solar cell, and more particularly, to a tandem solar cell and a method for manufacturing the tandem solar cell, wherein the horizontal resistance of a composite layer connecting an upper cell and a lower cell of the tandem solar cell can be reduced to minimize the occurrence of a shunt path, thereby preventing a decrease in composite efficiency due to electron transfer problems, and the absorption rate in a short wavelength range is low, thereby improving the current value when applied to the tandem solar cell. Background Art
[0003] Multi-junction (tandem) solar cells attempt to efficiently utilize solar energy over a wide wavelength range by vertically stacking light absorbing layers with different band gaps, thereby minimizing thermalization losses. Specifically, tandem solar cells allow light absorbing layers with different band gaps to absorb sunlight by dividing it into wavelength regions, so that when photons with energy greater than the band gap in a single-junction solar cell are absorbed by the light absorbing layer, the efficiency limit of a single-junction solar cell can be overcome by minimizing the loss of excess energy of electrons and holes as heating energy. Recently, due to the growing interest in tandem solar cells as the most viable next-generation solar cell, competition for the research and development of tandem solar cell technology with various structures has become increasingly fierce worldwide.
[0004] Meanwhile, in such tandem solar cells, a transparent conductive film (TCO) is mainly used as a composite layer that electrically connects the silicon lower cell and the perovskite upper cell. The transparent conductive film has such a characteristic that when the free charge concentration is low, grain boundary scattering caused by the energy barrier (potential barrier) formed by the free charges trapped at the grain boundaries plays a significant role, resulting in an extremely low mobility of the free charges. On the other hand, if the free charge concentration is large, the number of free charges that can overcome the energy barrier formed at the grain boundaries increases, and thus the mobility of the free charges can be increased to a certain extent. In this case, if the free charge concentration increases above a certain level, as the ionized impurities present in the film increase, scattering may occur between the free charges and the ionized impurities, resulting in a decrease in the mobility of the free charges.
[0005] In order to compensate for this problem, various studies have been conducted to generate free charges by doping cationic metal elements and to control the free charge concentration by adjusting the doping amount as a method of increasing the free charge concentration in a transparent conductive film used as a composite layer in a tandem solar cell. In addition, conventional tandem solar cells use ITO with a ratio of 10wt% SnO2 and 90wt% In2O3 or IZO with a ratio of 10wt% ZnO2 and 90wt% In2O3, which have higher conductivity, as a transparent conductive film in the composite layer.
[0006] However, in the case of a composite layer having such a ratio, the resistance is low and thus electrons can move efficiently, but there is a limit to improving the efficiency of the tandem solar cell due to the following problem.
[0007] First, in the case of a tandem solar cell using a conventionally introduced transparent conductive film having the above ratio as a composite layer, there is a problem of generating a shunt path and causing a loss. That is, in a tandem solar cell in which a lower silicon cell and an upper perovskite layer are connected in series through a composite layer, if the horizontal conductivity of the composite layer is low, charges flow horizontally and generate a shunt path, resulting in electrical loss. Due to this electrical loss, there is a limit to improving the efficiency of solar cells.
[0008] Secondly, when ITO with a ratio of 10wt% In2O3 is used as a transparent conductive film of the composite layer, there is a limitation on minimizing light loss due to the absorption phenomenon of ionized impurities in the visible light range and the free carrier absorption phenomenon in the long wavelength range and near infrared range of visible light, which leads to increased light absorption. In other words, there is a problem that a tandem solar cell having a structure in which an upper cell with a large band gap absorbs solar energy in a low wavelength range and a lower cell with a small band gap absorbs solar energy in a high wavelength range has a limitation in reducing light loss, and thus cannot utilize solar energy in a wide wavelength range.
[0009] Therefore, by exhibiting higher sheet resistance, lower conductivity, and lower electron mobility in the composite layer connecting the upper cell and the lower cell of the tandem solar cell compared to the prior art, the efficiency reduction due to the shunt path can be minimized, thereby preventing the reduction of recombination and the decrease in efficiency due to the limited horizontal movement of electrons. In addition, since it has a low absorptivity in the short wavelength band, it is expected to increase the current value when applied to the tandem solar cell. Therefore, there is an urgent need to study tandem solar cells that can improve the efficiency of tandem solar cells. Summary of the invention
[0010] Technical issues
[0011] The present invention is made to overcome the above-mentioned problems, and the problem to be solved by the present invention is to provide a series solar cell and a method for manufacturing the series solar cell, which can increase the horizontal resistance by using a transparent conductive film element with a specific ratio as a composite layer connecting the upper cell and the lower cell of the series solar cell, thereby minimizing the efficiency reduction caused by the shunt path.
[0012] In addition, another problem to be solved by the present invention is to provide a tandem solar cell and a method for manufacturing the tandem solar cell, which can prevent the reduction of recombination and the decrease of efficiency due to the limited electron movement, and due to the low absorption in the short wavelength band, when applied to the tandem solar cell, it can be expected to increase the current value, thereby improving the efficiency of the tandem solar cell.
[0013] Technical Solution
[0014] In order to solve the above problems, a tandem solar cell is provided, comprising: a silicon lower cell; a perovskite upper cell; and a composite layer connecting the silicon lower cell and the perovskite upper cell, wherein the composite layer comprises ITO as a transparent conductive film, and the ITO comprises SnO2 and In2O3 in a weight ratio of 18 to 21:79 to 82.
[0015] In addition, according to the embodiment of the present invention, the thickness of the transparent conductive film may be 5 to 50 nm.
[0016] In addition, the transparent conductive film may have a sheet resistance of 50 ohm / sq to 1 M ohm / sq.
[0017] In addition, the silicon lower cell may be any one selected from the group consisting of Al-BSF, PERC, PERT, PERL, and TOPCon structures.
[0018] In addition, the conductivity of the transparent conductive film is 600 1 / ohm·cm to 1200 1 / ohm·cm.
[0019] In addition, the electron mobility of the transparent conductive film is 60 cm 3 / Vs to 120 cm 3 / Vs.
[0020] In addition, the present invention provides a method for manufacturing a tandem solar cell, comprising: step 1, forming a composite layer on the upper surface of a silicon lower cell; and step 2, forming a perovskite upper cell connected to the silicon lower cell through the composite layer, wherein the composite layer includes ITO as a transparent conductive film, and the ITO includes SnO2 and In2O3 in a weight ratio of 18 to 21:79 to 82.
[0021] Meanwhile, this invention was researched with the support of the following Korean R&D projects.
[0022] 1. [National R&D project supporting this invention]
[0023] [Project Identification Number] 1415174234
[0024] [Project number] 20203040010320
[0025] [Department Name] Ministry of Trade, Industry and Energy
[0026] [Name of project management (professional) institution] Korea Institute of Energy Technology Evaluation and Planning
[0027] [Research Project Name] New Energy and Renewable Energy Core Technology Development
[0028] [Research Task Name] Development of 6-inch perovskite / crystalline silicon tandem solar cell manufacturing technology with 26% higher efficiency for increased power generation
[0029] [Contribution rate] 1 / 2
[0030] [Name of mission execution organization] Hanwha Solutions Co., Ltd.
[0031] [Study period] January 1, 2022 to December 31, 2022
[0032] 2. [National R&D project supporting this invention]
[0033] [Project Identification Number] 1415176482
[0034] [Project number] 20213030010400
[0035] [Department Name] Ministry of Trade, Industry and Energy
[0036] [Name of project management (professional) institution] Korea Institute of Energy Technology Evaluation and Planning
[0037] [Research Project Name] New Energy and Renewable Energy Core Technology Development (R&D)
[0038] [Research Task Name] Development of high-efficiency, durable perovskite / crystalline silicon tandem solar cell module process technology
[0039] [Contribution rate] 1 / 2
[0040] [Name of mission execution organization] Hanwha Solutions Co., Ltd.
[0041] [Study period] May 1, 2022 to December 31, 2022
[0042] Beneficial Effects
[0043] Compared with the prior art, the present invention can improve the horizontal resistance by exhibiting higher sheet resistance, lower conductivity, and lower electron mobility in the composite layer connecting the upper cell and the lower cell of the tandem solar cell, thereby minimizing the efficiency reduction caused by the shunt path, and can prevent the reduction of recombination and the reduction of efficiency due to the limited electron movement. Moreover, since it has low absorption in the short wavelength range, when applied to the tandem solar cell, it can be expected to increase the current value, thereby improving the efficiency of the tandem solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a simulation diagram of a tandem solar cell device according to an embodiment of the present invention.
[0045] Figure 2 is a graph showing transparent conductive film properties of composite layers according to embodiments of the present invention and comparative examples.
[0046] Figure 3 is a graph showing the cell efficiency of the tandem solar cell devices according to the examples of the present invention and the comparative examples. DETAILED DESCRIPTION
[0047] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily practice the present invention. The present invention can be implemented in many different forms and is not limited to the embodiments described herein.
[0048] As described above, there is a limit to improving the efficiency of conventional tandem solar cells due to electrical / optical losses of a transparent conductive film used in a composite layer connecting an upper cell and a lower cell.
[0049] Therefore, in order to solve the above problems, the present invention attempts to solve the above problems by providing a tandem solar cell, which includes a silicon lower cell, a perovskite upper cell, and a composite layer connecting the silicon lower cell and the perovskite upper cell, wherein the composite layer is ITO as a transparent conductive film and has SnO2 and In2O3 in a weight ratio of 18 to 21:79 to 82.
[0050] Therefore, compared with the prior art, the present invention can improve the horizontal resistance by exhibiting higher sheet resistance, lower conductivity, and lower electron mobility in the composite layer connecting the upper cell and the lower cell of the series solar cell, thereby minimizing the efficiency reduction caused by the shunt path, and can prevent the reduction of recombination and the reduction of efficiency due to the limited electron movement, and because it has low absorption in the short wavelength range, when applied to the series solar cell, it can be expected to increase the current value, thereby being able to improve the efficiency of the series solar cell.
[0051] In this specification, the lower cell refers to a silicon solar cell formed at the bottom of the tandem solar cell, and the upper cell refers to a perovskite solar cell formed at the top of the tandem solar cell.
[0052] Furthermore, in this specification, a silicon lower cell refers to a solar cell including silicon as a light absorbing layer, and a perovskite upper cell refers to a solar cell including a material having a perovskite structure as a light absorbing layer.
[0053] Hereinafter, a tandem solar cell device according to the present invention will be described in detail with reference to the accompanying drawings.
[0054] The tandem solar cell device 100 according to the present invention includes a silicon lower cell 200 , a perovskite upper cell 400 , and a recombination layer 300 connecting the silicon lower cell 200 and the perovskite upper cell 400 .
[0055] The silicon lower cell 200 may be Figure 1 The emitter layer 220 is formed on an upper surface of the front electrode and may include a silicon layer 210 and an emitter layer 220 disposed on the silicon layer 210 .
[0056] The silicon layer 210 may have one of the structures of known silicon solar cells and is not limited to a specific structure. For example, the silicon layer 210 may include a crystalline silicon substrate (not shown), a p-type amorphous or crystalline silicon layer (not shown), an n-type amorphous or crystalline silicon layer (not shown), or an amorphous intrinsic silicon layer (not shown), and although not shown in the figure, may include additional layers as needed.
[0057] According to a preferred embodiment of the present invention, the structure of the silicon lower cell 200 may be changed to the following structure, such as by using n on the p-type silicon surface. ++ Al-BSF (aluminum back surface field) structure, PERC (passivated emitter and back cell), PERT (passivated emitter back full diffusion) and PERL (passivated emitter and back local diffusion) structure formed by emitter, or through SiOx tunneling layer / n ++ A TOPCon (Tunnel Oxide Passivation Contact) structure formed of polysilicon, etc., and there is no particular limitation.
[0058] At the same time, at least a portion of one surface or the other surface of the silicon layer 210 may be textured to improve light efficiency. That is, an uneven surface (not shown) is formed in the direction in which light enters, and the light scattering effect of light incident on the uneven surface increases the path of light incident on the silicon layer 210 to improve light collection, thereby increasing the absorption rate of sunlight.
[0059] Second, the recombination layer 300 serves as an intermediate layer that physically bonds and electrically connects the silicon lower cell 200 and the perovskite upper cell 400 , and it can perform charge recombination of the upper cell and the lower cell.
[0060] Typically, typical tandem solar cells attempt to improve the electrical / mechanical stability of tandem solar cells by improving the interface characteristics of the composite layer. To this end, conventional composite layers use a conductive material with light transmittance, and for example, use a TCO-based material (such as ITO (indium tin oxide), ICO (indium cerium oxide), IWO (indium tungsten oxide), ZITO (zinc indium tin oxide), ZIO (zinc indium oxide), ZTO (zinc tin oxide), GITO (gallium indium tin oxide), GIO (gallium indium oxide), GZO (gallium zinc oxide), AZO (aluminum-doped zinc oxide), FTO (fluorine tin oxide), ZnO, etc.), or use a nc-Si:H material layer.
[0061] Specifically, in order to control the free charge concentration and improve the efficiency of the tandem solar cells, ITO doped with cationic metal elements and with a controllable doping amount in a ratio of 10wt% SnO2 and 90wt% In2O3 or IZO in a ratio of 10wt% ZnO2 and 90wt% In2O3 is mainly used as a transparent conductive film of the composite layer.
[0062] However, in the case of a tandem solar cell using a previously introduced transparent conductive film having a corresponding ratio as a composite layer, there is a problem of generating a shunt path and causing a loss, and since free carrier absorption occurs in the long wavelength range of visible light and the near-infrared range, light absorption increases, so there is a limitation on minimizing light loss.
[0063] Therefore, the present invention solves the above-mentioned problems by forming SnO 2 and In 2 O 3 of ITO as the composite layer 300 into a transparent conductive film in a weight ratio of 18 to 21:79 to 82.
[0064] More specifically, referring to Table 2 and Figure 2 It can be seen that compared with the comparative example of the transparent conductive film corresponding to the conventional general weight ratio, the example 1 manufactured by using the transparent conductive film corresponding to the above numerical range has higher sheet resistance, lower conductivity and electron mobility. In addition, referring to Table 3 and Figure 3It can be seen that, compared with the comparative example of the transparent conductive film corresponding to the conventional general weight ratio, the examples manufactured using the transparent conductive film corresponding to the preferred numerical range of the present invention have improved JSC and FF at the same thickness.
[0065] Thus, the composite layer 300 according to the present invention is ITO as a transparent conductive film, and it can be seen that only when SnO2 and In2O3 are implemented to have a weight ratio of 18 to 21:79 to 82, the tandem solar cell can effectively play its role as a composite layer that physically / electrically connects the upper cell / lower cell and performs charge recombination.
[0066] In this case, if a transparent conductive film in which the weight ratio of SnO2 in the weight ratio of SnO2 and In2O3 in ITO is less than 18 or greater than 21 is used as the composite layer 300, the carrier concentration and electron mobility of the composite layer 300 will be greatly reduced, making it difficult to move the electrons generated in the lower battery, and thus there may be a problem that it cannot effectively play its role as a composite layer.
[0067] Meanwhile, the thickness of the transparent conductive film forming the composite layer 300 may be 5 to 50 nm, and more preferably 10 to 30 nm. If the thickness of the transparent conductive film forming the composite layer 300 exceeds 50 nm, there may be a problem of current loss due to increased parasitic absorption, and a problem of reduced efficiency due to a shunt path caused by reduced horizontal resistance. In addition, if the thickness of the transparent conductive film forming the composite layer 300 is less than 5 nm, reduced recombination and reduced efficiency may occur due to limited electron movement.
[0068] In addition, the sheet resistance of the transparent conductive film forming the composite layer 300 may be 50 ohm / sq to 1M ohm / sq, and more preferably 100 ohm / sq or more. In this case, if the sheet resistance of the transparent conductive film forming the composite layer 300 is less than 50 ohm / sq, the efficiency may be reduced due to the increase of the shunt path caused by the decrease in horizontal resistance, such as from Figure 2 and can be seen in the following Table 1. Meanwhile, when the sheet resistance of the film exceeds 1M ohm / sq, the conductivity in the vertical direction is significantly reduced, which can limit the electron movement, resulting in reduced recombination and reduced efficiency.
[0069] That is, when the present invention uses the transparent conductive film having the above-mentioned specific weight ratio to realize the composite layer 300 of the tandem solar cell, a transparent conductive film having a conductivity of 600 1 / ohm·cm to 1200 1 / ohm·cm can be manufactured, and more preferably, a transparent conductive film having a low conductivity of 700 1 / ohm·cm to 1100 1 / ohm·cm can be manufactured. Due to the effect of this low conductivity, the present invention is characterized in that a transparent conductive film having a conductivity of 60 cm 3 / Vs to 120 cm 3 / Vs and more preferably 70cm 3 / Vs to 110 cm 3 / Vs low electron mobility transparent conductive film.
[0070] Thus, the present invention can minimize the efficiency reduction due to the shunt path by increasing the horizontal resistance, and can also prevent the reduction of recombination and efficiency reduction due to the limited movement of electrons, and can show low absorption in the short wavelength range. Therefore, it can be expected to increase the current value of the series solar cell, thereby improving the efficiency of the series solar cell.
[0071] That is to say, referring to Figure 3 According to a preferred embodiment of the present invention, by ++ In the case of a TOP Perc / perovskite tandem device fabricated by depositing an ITO film of 20wt% SnO2:80wt% In2O3 on the emitter layer as a composite layer 300 to electrically connect the upper device and the lower device, it can be seen that both JSC and FF are improved at the same thickness, compared with a conventional structure in which an ITO film of 10wt% SnO2:90wt% In2O3 is applied as a composite layer.
[0072] Next, the perovskite upper cell 400 is an upper cell in contact with the silicon lower cell 200 , and a perovskite absorption layer 410 , an electron transport layer 420 , and a transparent conductive oxide electrode layer 430 may be stacked.
[0073] The perovskite absorption layer 410 may be formed so that hole-electron pairs generated by receiving light energy from the sun may be separated into electrons or holes. In one embodiment, electrons formed in the perovskite absorption layer 410 may be transferred to the electron transport layer 420, and holes formed in the perovskite absorption layer 410 may be transferred to the hole transport layer.
[0074] In this case, the perovskite absorption layer 410 may include an organic halide perovskite such as methylammonium iodide (MAI), formamidine iodide (FAI) or a metal halide perovskite such as lead iodide (PbI2), bromine iodide (PbBr) and lead chloride (PbCl2). That is, the perovskite absorption layer 410 may be a multilayer stack structure including at least one of an organic halide perovskite or a metal halide perovskite. More specifically, the perovskite absorption layer 410 may be represented by AMX3 (wherein A is a monovalent organic ammonium cation or a metal cation; M is a divalent metal cation; and X is a halogen anion). As a non-limiting example thereof, CH3NH3PbI3, CH3NH3PbI x Cl 3-x 、CH3NH3PbIxBr 3-x 、CH3NH3PbCl x Br 3-x , HC (NH2) 2PbI3, HC (NH2) 2PbIxCl 3-x , HC (NH2) 2PbIxBr3-x, HC (NH2) 2PbCl x Br 3-x ,, (CH3NH3) (HC (NH2) 2) 1-y PbI3, (CH3NH3) (HC (NH2)2) 1-y PbI x Cl 3-x , (CH3NH3) (HC (NH2) 2) 1-y PbI x Br 3-x , or (CH3NH3)(HC(NH2)2) 1-y PbCl x Br 3-x (0=x,y=1).
[0075] The electron transport layer 420 is used to separate and transport electrons formed in the perovskite absorption layer 410, and can be formed of a known or conventional material as long as it satisfies the purpose of the present invention. As a non-limiting example thereof, Ti oxide, Zn oxide, In oxide, Sn oxide, W oxide, Nb oxide, Mo oxide, Mg oxide, Zr oxide, Sr oxide, Yr oxide, La oxide, V oxide, Al oxide, Y oxide, Sc oxide, Sm oxide, Ga oxide, In oxide and SrTi oxide can be used.
[0076] Although the tandem solar cell device according to the present invention has been described above, this is merely an example, and an additional stacking structure capable of improving the efficiency of the solar cell may also be included.
[0077] The present invention will be described in more detail through the following examples, but the following examples do not limit the scope of the present invention but should be construed as helping to understand the present invention.
[0078] Example 1 - Fabrication of a tandem solar cell device
[0079] For the lower solar cell, a PERC structure cell manufactured by Hanwha Q CELLS is used, in which an n-type impurity-doped silicon substrate is formed by a POCl process. ++ An emitter layer is formed on the silicon substrate with a lower passivation layer and a lower electrode.
[0080] Next, by using a sputtering device ++ On top of the emitter layer, an ITO (indium tin oxide) layer with a thickness of 50 nm is formed as a composite layer.
[0081] Then, in n ++ An ITO film of 20wt% SnO2:80wt% In2O3 is deposited on the emitter layer to form a composite layer with a thickness of 20nm to electrically connect the upper / lower devices. Subsequently, NiO is formed using electron beam deposition under high vacuum conditions. x As a hole transport layer, and then IZO (indium doped zinc oxide) was formed with a thickness of 100 nm as a transparent electrode layer on the hole transport layer using a sputtering device.
[0082] Next, a TOPPerc / perovskite tandem device was fabricated by forming silver (Ag) with a thickness of 200 nm on top of the transparent electrode layer by using a thermal evaporator under high vacuum conditions.
[0083] In this case, in the case of an ITO thin film of 20 wt % SnO 2 : 80 wt % In 2 O 3 , its Sn / In ratio may be 18 wt % to 21 wt % according to a forming atmosphere, a forming method, and a post-treatment method.
[0084] Comparative Example 1
[0085] A TOPPerc / perovskite tandem device was manufactured in the same manner as in Example 1, except that an ITO film of a conventional numerical range of 10wt% SnO2:90wt% In2O3 was deposited and the composite layer electrically connecting the upper element and the lower element was formed to a thickness of 20nm.
[0086] Experimental Example 1-Evaluation of the properties of transparent conductive films
[0087] The film composition ratios of the composite layers of Examples 1 and 2 were evaluated using an XPS analysis device, and the results are shown in Table 1 below.
[0088] Referring to Table 1 below, in the case of the ITO film of 20wt% SnO2:80wt% In2O3 according to Example 1 of the present invention, it can be seen that it has a Sn / In ratio between 18wt% and 21wt%, depending on the formation atmosphere and formation method of the film and the post-treatment method.
[0089] [Table 1]
[0090]
[0091] Experimental Example 2-Evaluation of the properties of transparent conductive films
[0092] The properties of the films were evaluated for Example 1 and Comparative Example 1, and the results are shown in Tables 2 and Figure 2 As shown ( Figure 2 The vertical axis n refers to the refractive index, and k refers to the absorption coefficient).
[0093] Refer to Table 2 and Figure 2 In the case of Example 1 manufactured using the transparent conductive film corresponding to the preferred numerical range of the present invention, the sheet resistance (ohm / sq) is higher, and it can be seen that it has lower conductivity (1 / ohm·cm) and electron mobility (cm 3 / Vs).
[0094] [Table 2]
[0095]
[0096] Experimental Example 3-Evaluation of Solar Cell Efficiency
[0097] The photoelectric efficiency of the tandem solar cell devices according to Example 1 and Comparative Example 1 was measured using a solar simulator device under AM1.5G illumination conditions, and the results are shown in Tables 3 and 4 below. Figure 3 shown.
[0098] Refer to Table 3 and Figure 3 In the case of the example manufactured using the transparent conductive film corresponding to the preferred numerical range of the present invention, it can be seen that, compared with the comparative example corresponding to the conventional transparent conductive film having a general weight ratio, it has an improved short-circuit current density (J) at the same thickness. SC ) and fill factor (FF).
[0099] [Table 3]
[0100]
[0101] To summarize these results, the present invention can increase horizontal resistance by exhibiting higher sheet resistance, lower conductivity, and lower electron mobility in the composite layer connecting the upper cell and the lower cell of the tandem solar cell compared to the prior art, thereby minimizing the reduction in efficiency due to the shunt path. In addition, it is possible to prevent the reduction in recombination and the reduction in efficiency due to the limited movement of electrons, and since its absorption rate in the short wavelength range is low, when it is applied to the tandem solar cell, it is expected that the current value can be increased, and therefore it can be seen that the efficiency of the tandem solar cell can be improved.
Claims
1. A series solar cell comprising: Silicon lower cell; Perovskite top cell; as well as A composite layer connects the silicon lower cell and the perovskite upper cell, The composite layer includes ITO as a transparent conductive film, and the ITO includes SnO2 and In2O3 in a weight ratio of 18 to 21:79 to 82.
2. The tandem solar cell according to claim 1, wherein: The thickness of the transparent conductive film is 5 to 50 nm.
3. The tandem solar cell according to claim 1, wherein: The sheet resistance of the transparent conductive film is 50 ohm / sq to 1 M ohm / sq.
4. The tandem solar cell according to claim 1, wherein: The silicon bottom cell is any one selected from the group consisting of Al-BSF, PERC, PERT, PERL and TOPCon structures.
5. The tandem solar cell according to claim 1, wherein: The electrical conductivity of the transparent conductive film is 600 1 / ohm·cm to 1200 1 / ohm·cm.
6. The tandem solar cell according to claim 1, wherein: The electron mobility of the transparent conductive film is 60 cm 3 / Vs to 120 cm 3 / Vs.
7. A method for manufacturing a tandem solar cell, comprising: Step 1, forming a composite layer on the upper surface of the silicon lower cell; as well as Step 2, forming a perovskite upper cell, wherein the perovskite upper cell is connected to the silicon lower cell through the composite layer, The composite layer includes ITO as a transparent conductive film, and the ITO includes SnO2 and In2O3 in a weight ratio of 18 to 21:79 to 82.
Citation Information
Patent Citations
KRAS mutant protein inhibitor
KR1020220119088A